Phase Modulation of the Short-Latency Crossed Spinal Response in the Human Soleus Muscle - Stubbs, Peter W.; Nielsen, Jørgen F.; Sinkjær, Thomas; Mrachacz-Kersting, Natalie (Journal of neurophysiology, 2011)
Short-latency spinally mediated interlimb reflex pathways were recently reported between the left and right soleus muscles in the human lower-limb during sitting. The aim of the current study was to establish if these pathways were observed during a functional motor task such as human gait and modulated by the gait cycle phase and/or electrical stimulation intensity. The second aim was to elucidate on the afferents involved. Two interventions were investigated. First was ipsilateral tibial nerve (iTN) stimulation at motor threshold (MT), 35% of the maximal peak-to-peak M-wave (M-Max) and 85% M-Max (85M-Max) with stimuli applied at 60×, 70×, 80×, 90×, and 100% of the gait cycle of the ipsilateral leg. Second was ipsilateral sural nerve (SuN) and medial plantar nerve (MpN) stimulation at 1, 2, and 3 perceptual threshold at 90% of the gait cycle. The root mean squared (RMS) of the contralateral soleus (cSOL) responses were analyzed in a time window, 40–55 ms (or 45–60 ms for subjects >50 y/o) following iTN stimulation. The most consistent responses occurred at 90 and 100% of the gait cycle at higher stimulation intensities of the iTN. Significantly inhibitory responses ( P = 0.006) were reported at 60 versus 80% ( P = 0.03), 90% ( P = 0.006), and 100% ( P = 0.002) and 70 versus 90% ( P = 0.02) and 100% ( P = 0.009) of the gait cycle at 85M-Max. The responses became more inhibitory with increasing stimulation intensities at 80% ( P = 0.01), 90% ( P = 0.001), and 100% ( P = 0.004) of the gait cycle. Stimulation of the MpN and SuN at all stimulation intensities demonstrated no short-latency responses. Therefore, it is unlikely that afferents within these nerves contribute to the response. This is the first study to show short-latency spinally mediated responses in the cSOL following iTN stimulation, during walking. It provides evidence for a new spinal pathway contributing to motor control and demonstrates that the response likely has functional relevance.